In vitro single-unit recordings reveal increased peripheral nerve conduction velocity by focused pulsed ultrasound. (3rd May 2018) - Ilham, S J; Chen, L; Guo, T; Emadi, S; Hoshino, K; Feng, B
Abstract: Ultrasound that is widely used in medical diagnosis has drawn growing interests as a noninvasive means of neuromodulation. Focused pulsed ultrasound (FPUS) effectively modulates neural encoding and transmission in the peripheral nervous system (PNS) with unclear mechanism of action, which is further confounded by contradictory experimental outcomes from recordings of compound action potentials (CAP). To address that, we developed a novel in vitro set up to achieve simultaneous single-unit recordings from individual mouse sciatic nerve axon and systematically studied the neuromodulation effects of FPUS on individual axon. Unlike previous CAP recordings, our single-unit recordings afford superior spatial and temporal resolution to reveal the subtle but consistent effects of ultrasonic neuromodulation. Our results indicate that, (1) FPUS did not evoke action potentials directly in mouse sciatic nerve at all the tested intensities (spatial peak temporal average intensity, ISPTA of 0.91 to 28.2 W/cm 2 ); (2) FPUS increases the nerve conduction velocity (CV) in both fast-conducting A- and slow-conducting C- type axons with effects more pronounced at increased stimulus duration and intensity; and (3) effects of increased CV is reversible and cannot be attributed to the change of local temperature. Our results support existing theories of non-thermal mechanisms underlying ultrasonic neuromodulation with low-intensity FPUS, including NICE, flexoelectricity, and solition models. This work also provides a solid experimental basis to further advance our mechanistic understandings of ultrasonic neuromodulation in the PNS.